Transcriptional response after exposure to domoic acid-producing Pseudo-nitzschia in the digestive gland of the mussel Mytilus galloprovincialis. (15th December 2017) - Pazos, Antonio J.; Ventoso, Pablo; Martínez-Escauriaza, Roi; Pérez-Parallé, M. Luz; Blanco, Juan; Triviño, Juan C.; Sánchez, José L.
Abstract: Bivalve molluscs are filter feeding species that can accumulate biotoxins in their body tissues during harmful algal blooms. Amnesic Shellfish Poisoning (ASP) is caused by species of the diatom genus Pseudo-nitzschia, which produces the toxin domoic acid. The Mytilus galloprovincialis digestive gland transcriptome was de novo assembled based on the sequencing of 12 cDNA libraries, six obtained from control mussels and six from mussels naturally exposed to domoic acid-producing diatom Pseudo-nitzschia australis . After de novo assembly 94, 727 transcripts were obtained, with an average length of 1015 bp and a N50 length of 761 bp. The assembled transcripts were clustered (homology > 90%) into 69, 294 unigenes. Differential gene expression analysis was performed (DESeq2 algorithm) in the digestive gland following exposure to the toxic algae. A total of 1158 differentially expressed unigenes (absolute fold change > 1.5 and p-value < 0.05) were detected: 686 up-regulated and 472 down-regulated. Several membrane transporters belonging to the family of the SLC (solute carriers) were over-expressed in exposed mussels. Functional enrichment was performed using Pfam annotations obtained from the genes differentially expressed, 37 Pfam families were found to be significantly (FDR adjusted p-value < 0.1) enriched. Some of these families (sulfotransferases, aldo/keto reductases, carboxylesterases, C1q domain and fibrinogen C-terminal globular domain) could be putatively involved in detoxification processes, in the response against of the oxidative stress and in immunological processes. Protein network analysis with STRING algorithm found alteration of the Notch signaling pathway under the action of domoic acid-producing Pseudo-nitzschia . In conclusion, this study provides a high quality reference transcriptome of M. galloprovincialis digestive gland and identifies potential genes involved in the response to domoic acid. Graphical abstract: Highlights: Mussels were naturally exposed to domoic acid-producing Pseudo-nitzschia. 1158 unigenes were differentially expressed. 37 Pfam families were found to be significantly enriched. Some of these families could be involved in detoxification, response against oxidative stress and/or immunological processes. Protein network analysis found alteration of the Notch signaling pathway.